2021
DOI: 10.1016/j.heliyon.2021.e06600
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite nanoparticles grafted with murexide-terminated polyamidoamine dendrimers for removal of lead (II) from aqueous solution: synthesis, characterization, adsorption and antimicrobial activity studies

Abstract: In this study, new, efficient, eco-friendly and magnetically separable nanoadsorbents, MNPs-G1-Mu and MNPs-G2-Mu, were successfully prepared by covalently grafting murexide-terminated polyamidoamine dendrimers on 3-aminopropyl functionalized silica-coated magnetite nanoparticles, and used for rapid removal of lead (II) from aqueous medium. After each adsorption process, the supernatant was successfully acquired from reaction mixture by the magnetic separation, and then analyzed by employing ICP-OES. Chemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…The results of adsorption kinetic experiments were studied by four models: the pseudo-rst-and second-order, intraparticle, and Elovich models. Pseudo-rst-order, eqn (3) presumes that the sorption rate depends on the removal capacity. 33 log(q e À q t ) ¼ log q e À (K 1 /2.303)t…”
Section: Adsorption Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of adsorption kinetic experiments were studied by four models: the pseudo-rst-and second-order, intraparticle, and Elovich models. Pseudo-rst-order, eqn (3) presumes that the sorption rate depends on the removal capacity. 33 log(q e À q t ) ¼ log q e À (K 1 /2.303)t…”
Section: Adsorption Calculationsmentioning
confidence: 99%
“… 2 It can cause damage to brain cortex cells, the nervous system, sensory disturbance, and other symptoms. 3 Thus, the removal of lead and other heavy metals from water streams is a vital necessity. Until now, conventional methods to remove heavy metals include coagulation, 4 precipitation, chemical reduction, 5 ion exchange, 6 biological treatment, 7 membrane separation, 8 and filtration.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the composite adsorbent obtained by modifying magnetic nano-material with PAMAMs has a certain potential application value for the development of heavy metal adsorption research. Ekinci et al (2021) successfully prepared magnetically separable nanoadsorbents 2016) had grown the adsorbent formed by the thirdgeneration-PAMAM dendritic structure on superparamagnetic epoxy polymer composites by soap-free emulsion polymerization procedure to remove U 6+ , and the results showed that there was no significant loss of adsorption capacity after five adsorption cycles. All these reflect that polyamide-amines composite can achieve effective and regenerative effect in the removal of heavy metal ions.…”
Section: Pamams/magnetic Nanomaterials Compositesmentioning
confidence: 99%
“…This composite powder is utilized for electrophotographic (EP) printing. [30,31] Printer toner is an inexpensive material and particular toner material is needed for each printer and copier. Hence, differences in terms of stability are observed related to the size and chemical composition of the toner particles.…”
Section: Introductionmentioning
confidence: 99%